Short-term daily steps increment enhances submaximal exercise tolerance in healthy insuficiently active men - Porto, Luiz (2014)
The 10000 steps/day message has been proposed as a minimum steps/day target for healthy adults. Nevertheless, this target does not seem feasible as an initial goal for inactive adults. New strategies to progressively increase daily steps should be evaluated. The study evaluated the effectiveness of increase a pedometer-measured 3500 steps/day on physical performance at anaerobic threshold (AT). Nineteen healthy insufficiently active men, 19-46 yrs, wore a pedometer for 2 weeks to quantify their habitual daily steps at baseline. Afterwards, subjects were instructed to increase 3500 steps/day above baseline during 3 weeks (intervention). Cardiopulmonary exercise stress tests (CPX) were performed before and after the intervention. Submaximal exercise tolerance was analyzed by the heart rate at AT (HR-AT), the oxygen uptake at AT (VO2-AT), the time spent on CPX until AT onset and the reached distance. Nonparametric statistics were applied, expressing the results as median and minimum and maximum values. The variables were pair-wised compared by the Wilcoxon test. The differences were considered statistically significant when a two-tailed P-value was less than 5%. At baseline, median (min-max) of daily steps was 7295 (4700–14752 steps), whereas it was 11772 (8998–18620 steps) after the intervention (p=0.0001). On CPX, time until AT onset was higher after (359s; 179-521s) than before daily steps improvement (340s; 208-436s) (p=0.027). Similarly, the distance attained at AT was higher after (398.6m; 165.6–637.5m) than before the intervention (372.2m; 197.8–528.8m) (p=0.014). The increment of 3500 steps/day above baseline, during three weeks, was effective for improving exercise tolerance at AT.